2010
DOI: 10.1021/bm100237r
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal DNA Carriers for Direct Localization in Cell Compartments by pH Sensoring

Abstract: Multifunctional colloidal microparticles allow the integration of various active agents as well as reporter molecules into one system without interfering combining delivery and sensing functions. In this study, calcium carbonate particles were functionalized with fluorescein isothiocyanate-labeled poly(allylamine hydrochloride) (FITC-PAH) allowing particle localization in cell compartments of different pH. Plasmid DNA (pEGFP-C1 and pDsRed1-N1) as a reporter agent for drug release in the cytoplasm and rhodamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…Gene expression has also recently been reported following delivery of core encapsulated mRNA after laser triggered release from synthetic microcapsules [27]. Interestingly, studies by Reibetanz et al (2006) with LbL (protamine and DS) microcapsules assembled on a silica core or a retained CaCO 3 core also demonstrate plasmid transfection from a subouter layer (8th of 9) [6,28]. In one of these studies transfection is also reported from a middle layer (8th of 11) [28].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Gene expression has also recently been reported following delivery of core encapsulated mRNA after laser triggered release from synthetic microcapsules [27]. Interestingly, studies by Reibetanz et al (2006) with LbL (protamine and DS) microcapsules assembled on a silica core or a retained CaCO 3 core also demonstrate plasmid transfection from a subouter layer (8th of 9) [6,28]. In one of these studies transfection is also reported from a middle layer (8th of 11) [28].…”
Section: Discussionmentioning
confidence: 90%
“…LbL assembled capsules also have the potential to enter cells where they can in their simplest form deliver a cargo with gradually controlled or stimuli-triggered release as well as act as cell residing biosensors to report on intracellular processes [5,6], for recent review on biological application of LbL see [7,8]. These capsules also have the potential to be engineered with multiple activities by incorporating molecules with distinct activities into different layers or within the capsule core.…”
Section: Introductionmentioning
confidence: 99%
“…In the co-immunoprecipitation assay, the full open reading frame of the human FXR1 gene and human BTF gene were inserted into the pCMV-HA vector [15] and the pCMV-Myc vector [21], respectively, to generate recombinant vector pCMV-HA-FXR1 and pCMV-Myc-BTF (Table 1). Similarly, in the co-localization assay, the full open reading frames of the human FXR1 gene and human BTF gene were inserted into the pEGFP-C1vector [22] and pDsRed-Monomer-N1 vector [23] to generate the expression vector pEGFP-N1-FXR1 and pDsRed-Monomer-N1-BTF (Table 1), respectively.…”
Section: Plasmidsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Charged PE shells, which may encapsulate pHsensitive fluorescent dyes, generate electric fields that can cause deviations in local ion distributions and limit practical applications. Previous experiments 15,16 and theories 17,18 demonstrated that the pH and ion densities near a charged flat surface can deviate from their bulk values.…”
Section: Introductionmentioning
confidence: 99%